Analysis of Healthy Food Menu at SaladBar by Hadikitchen, Mall Kelapa Gading - Baskoro Harwindito; Laurensia Angela Patty; Hady Chandra Kurniawan; Aang Sunarto (International Journal of Travel, Hospitality and Events, 2022)
Purpose : The menu is a list of human foods that are displayed, healthy food aims to make the body feel comfortable, have more energy for activities and avoid disease, indicators of healthy food, namely, a plant-based diet, high antioxidants and animal protein, food is a basic need that is needed at all times . This study will discuss the potential contained in healthy food menus in restaurants and draw conclusions from the results, to find out healthy food is a trend icon for one of the consumers and the SaladBar by Hadikitchen conceptualizes a healthy food menu for consumers. Research methods: Research method uses a qualitative descriptive analysis method with an interactive data analysis technique approach, from observation, interviews, documentation, data reduction, presentation, drawing conclusions and is included with the validity of the data, namely validity and reliability tests. Results and Discussions: A healthy lifestyle is something that cannot be abandoned by everyone, this lifestyle is a trend in the present time, because in this era there continue to be many new diseases, healthy in the fundamental sense is all the things that are trying to share good results or consequences for our body, a healthy lifestyle is something that is very suitable for doing our life, on the contrary, a healthy lifestyle is a path that must be taken to get a healthy body physically and spiritually. Implication: The healthy food menu is a consumer icon trend because of its unique use of raw materials. Keywords: restaurant, menu, healthy food.